Ensembl 2021. Issue Volume 49:Issue D1(2021) (2nd November 2020) - Howe, Kevin L; Achuthan, Premanand; Allen, James; Allen, Jamie; Alvarez-Jarreta, Jorge; Amode, M Ridwan; Armean, Irina M; Azov, Andrey G; Bennett, Ruth; Bhai, Jyothish; Billis, Konstantinos; Boddu, Sanjay; et al.
Abstract: The Ensembl project (https://www.ensembl.org ) annotates genomes and disseminates genomic data for vertebrate species. We create detailed and comprehensive annotation of gene structures, regulatory elements and variants, and enable comparative genomics by inferring the evolutionary history of genes and genomes. Our integrated genomic data are made available in a variety of ways, including genome browsers, search interfaces, specialist tools such as the Ensembl Variant Effect Predictor, download files and programmatic interfaces. Here, we present recent Ensembl developments including two new website portals. Ensembl Rapid Release (http://rapid.ensembl.org ) is designed to provide core tools and services for genomes as soon as possible and has been deployed to support large biodiversity sequencing projects. Our SARS-CoV-2 genome browser (https://covid-19.ensembl.org ) integrates our own annotation with publicly available genomic data from numerous sources to facilitate the use of genomics in the international scientific response to the COVID-19 pandemic. We also report on other updates to our annotation resources, tools and services. All Ensembl data and software are freely available without restriction.